1995
DOI: 10.1161/01.cir.91.4.941
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Endothelin-1 Immunoreactivity in the Active Coronary Atherosclerotic Plaque

Abstract: Endothelin-1 immunostaining of atherosclerotic tissue localizes predominantly with plaque components indicative of chronic inflammatory processes. The increased tissue endothelin-1-like immunoreactivity in active coronary atherosclerotic lesions may provide a clue to the mechanisms of increased vasoreactivity of the culprit lesion in acute ischemic syndromes, which is the clinical substrate of the active coronary atherosclerotic plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(82 citation statements)
references
References 47 publications
4
78
0
Order By: Relevance
“…Moreover, the release of the potent vasoconstrictor endothelin-1, which is characteristic of endothelial dysfunction, is enhanced at the site of the unstable plaque, further mediating focal vasoconstriction and myocardial ischemia. 24,25 The enhanced vasoconstriction at the site of the active plaque may escalate further in response to such stimuli as physical and mental stress, which mediate vasoconstriction via an endothelium-dependent mechanism.…”
Section: Vasoconstrictionmentioning
confidence: 99%
“…Moreover, the release of the potent vasoconstrictor endothelin-1, which is characteristic of endothelial dysfunction, is enhanced at the site of the unstable plaque, further mediating focal vasoconstriction and myocardial ischemia. 24,25 The enhanced vasoconstriction at the site of the active plaque may escalate further in response to such stimuli as physical and mental stress, which mediate vasoconstriction via an endothelium-dependent mechanism.…”
Section: Vasoconstrictionmentioning
confidence: 99%
“…56 Tissue ET levels have been shown to correlate with the severity of angina in patients with coronary artery disease and increase in patients with unstable angina. 57,58 ET-1 plasma levels have also been found to be elevated in patients with acute myocardial infarction and correlate with 1-year prognosis. 59 No clinical trials have yet been conducted to evaluate the effect of ET receptor blockade on the development of chronic atherosclerotic vascular disease.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Although ET-1 was initially discovered as a product of endothelial cells, 34 it is also secreted by macrophages and activated vascular smooth muscle cells. 10,[35][36][37] Recent evidence evaluating the expression of coronary ET-1 at different stages of atherosclerosis reveals that ET-1 expression increases with progression of atherosclerotic lesions, and ET-1 immunoreactivity is particularly elevated in the presence of inflammation. 36,37 Indeed, we have previously shown that endogenous ET-1 contributes to vasomotor tone in atherosclerotic coronary arteries.…”
Section: Role Of Endothelin In Hypercholesterolemiamentioning
confidence: 99%